2013
DOI: 10.3201/eid1909.130130
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Chikungunya Virus Infection, Vanimo, Papua New Guinea

Abstract: In June 2012, health authorities in Papua New Guinea detected an increase in febrile illnesses in Vanimo. Chikungunya virus of the Eastern/Central/Southern African genotype harboring the E1:A226V mutation was identified. This ongoing outbreak has spread to ≥8 other provinces and has had a harmful effect on public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…Nucleotide and amino acid identity among the consensus sequences from these individuals was >99.9%. The MCC phylogeny showed that the Dominican Republic sequences clustered within the Asian lineage together with other Caribbean sequences isolated in 2014 [11, 16]. The most closely related Asian sequences circulated between 2012 and 2013 in Micronesia, the Philippines and China.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Nucleotide and amino acid identity among the consensus sequences from these individuals was >99.9%. The MCC phylogeny showed that the Dominican Republic sequences clustered within the Asian lineage together with other Caribbean sequences isolated in 2014 [11, 16]. The most closely related Asian sequences circulated between 2012 and 2013 in Micronesia, the Philippines and China.…”
Section: Supporting Informationmentioning
confidence: 99%
“…CHIKV is a re-emerging mosquito-transmitted member of the genus Alphavirus (family Togaviridae) that causes sporadic epidemics of primarily rheumatic disease, with the largest epidemic ever recorded starting in 2004 in Africa and spreading across Asia (Suhrbier et al, 2012), recently reaching Oceania (Horwood et al, 2013) and affecting millions of people. The recent explosive outbreak in the Caribbean (Leparc-Goffart et al, 2014) was the first in the western hemisphere and has even reached the USA (McCarthy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…CHIKV caused an explosive outbreak of disease beginning in 2004 that expanded to areas beyond the historical range of the virus, including Europe and many islands in the Indian Ocean (1,2,13), and produced more-severe illness than previously observed (14)(15)(16)(17). CHIKV continues to spread to new regions (18)(19)(20)(21)(22), and currently there are no available vaccines or treatments for this disease (23).…”
mentioning
confidence: 99%